Pengaruh Keterampilan Komunikasi Interpersonal dan Kepercayaan Diri Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Kimia - Ariria, Amna; Anwar S, Lenny; Albeta, Sri Wilda (Jurnal Pendidikan Kimia Universitas Riau, 2025)
This research aims to determine the influence of interpersonal communication skills and self-confidence on 10th-grade students' chemistry learning outcomes, both partially and simultaneously, at SMA Negeri 4 Pekanbaru. This type of research is a survey study with a quantitative approach. The data collection methods used in this study are questionnaires and documentation. The validated questionnaires on interpersonal communication skills and self-confidence were distributed to a sample of 200 students selected using the simple random sampling technique. Data on chemistry learning outcomes were collected through documentation. The data analysis methods applied in this study were simple and multiple linear regression analyses. The results showed that (1) there is a positive and significant influence of interpersonal communication skills on chemistry learning outcomes, (2) there is a positive and significant influence of self-confidence on chemistry learning outcomes, and (3) there is a positive and significant simultaneous influence of interpersonal communication skills and self-confidence on chemistry learning outcomes.